The Impact of Interlayer Electronic Coupling on Charge Transport in Organic Semiconductors: A Case Study on Titanylphthalocyanine Single Crystals. Issue 17 (17th March 2016) - Zhang, Zongpeng; Jiang, Lang; Cheng, Changli; Zhen, Yonggang; Zhao, Guangyao; Geng, Hua; Yi, Yuanping; Li, Liqiang; Dong, Huanli; Shuai, Zhigang; Hu, Wenping
Abstract: Traditionally, it is believed that three‐dimensional transport networks are preferable to those of lower dimensions. We demonstrate that inter‐layer electronic couplings may result in a drastic decrease of charge mobilities by utilizing field‐effect transistors (FET) based on two phases of titanyl phthalocyanine (TiOPc) crystals. The α‐phase crystals with electronic couplings along two dimensions show a maximum mobility up to 26.8 cm 2 V −1 s −1 . In sharp contrast, the β‐phase crystals with extra significant inter‐layer electronic couplings show a maximum mobility of only 0.1 cm 2 V −1 s −1 . Theoretical calculations on the bulk crystals and model slabs reveal that the inter‐layer electronic couplings for the β‐phase devices will diminish remarkably the device charge transport abilities owing to the coupling direction perpendicular to the current direction. This work provides new insights into the impact of the dimensionality and directionality of the packing arrangements on charge transport in organic semiconductors. Abstract : Molecular packing motifs play a key role in determining the charge‐transport properties of molecular materials. Interlayer electronic couplings perpendicular to the current direction result in a drastic decrease of charge mobilities, shown by utilizing field‐effect transistors. α‐Phase TiOPc crystals (see picture; left) show a maximum mobility μmax more than 250 times that of the β‐phase.